Using Lu Xun’s Literature to Enhance Critical Reading and Intercultural Understanding in a Secondary School Chinese Language Course in Thailand - Thirawutthichai, Saranphong; Cheng, Zhang Zi (วารสารครุศาสตร์ ราชภัฏเชียงใหม่, 2026)
This study aimed to examine the effects of integrating Lu Xun’s literature into secondary Chinese language instruction in Thailand, focusing on students’ reading comprehension, intercultural understanding, and critical thinking. A mixed-methods design was employed with 54 Grade 12 students over six weeks. Participants engaged with adapted literary texts and completed 1) pre- and post-tests assessing reading comprehension, 2) an intercultural awareness questionnaire, and 3) a critical thinking questionnaire, along with 4) semi-structured interviews. Quantitative data was analyzed using paired-sample t-test. Quantitative results showed statistically significant improvements across all domains, supported by large effect sizes. Furthermore, qualitative data was analyzed using thematic analysis. Qualitative findings revealed that students enhanced their reading strategies, reflected critically on cultural similarities and differences, and demonstrated increased independent thinking. Literature-based instruction can broaden Chinese secondary students’ cognitive and cultural skills, challenging the traditionally utilitarian focus in Thai secondary curricula. Using authentic texts and themes fosters deeper engagement and helps develop more critical, culturally aware learners. Limitations regarding sample size, self-reported measures, and intervention duration are acknowledged, and recommendations for future research are proposed.